POLITENESS STRATEGIES IN DIPLOMATIC SPEECHES: A PRAGMATIC ANALYSIS - Claire Dubois (International Journal of Literature and Language Studies, 2026)
This article examines politeness strategies in diplomatic speeches delivered in international forums. The study responds to the problem that diplomatic language is frequently described as formal or indirect, but the pragmatic choices that preserve face while expressing disagreement require closer analysis. Using qualitative pragmatic analysis using politeness theory and speech-act classification, the article analyzes twenty publicly available diplomatic speeches from multilateral meetings. The findings indicate that speakers balanced positive politeness, hedging, inclusive pronouns, and indirect criticism to project cooperation while protecting national positions. The article argues that politeness in diplomacy is a strategic discourse practice that shapes both interpersonal respect and geopolitical positioning. By connecting language, literary form, and interpretation, the study offers a concise contribution to current debates in literature and language studies.